Depression and coronary heart disease: A review of the epidemiological evidence, explanatory mechanisms and management approaches - Goldston, Kerrie; Baillie, Andrew J. (Clinical psychology review, 2008)
There is compelling evidence that depression is an independent risk factor for both the development of Coronary Heart Disease (CHD) and for worsening prognosis once CHD is established. Given the increasing awareness of the high prevalence of co-morbid depression in individuals with CHD, clinical psychologists are likely to become increasingly involved in the care of cardiac patients. It is imperative therefore, that they are aware of the complex relationship between depression and CHD and are familiar with the pharmacological and psychological interventions most likely to be effective in these patients. The following review explores the epidemiological evidence for the relationship between depression and CHD, examines the biological, behavioral and social mechanisms that may account for this relationship, and considers the findings of the psychological and pharmacological intervention trials seeking to improve outcomes for depressed cardiac patients. Collaboration across a range of disciplines is needed to establish a program of research and professional education and to develop clinical practice guidelines and pathways which support the implementation of best practice in the assessment and management of co-morbid depression in people with and at risk of CHD. Clinical psychologists are well-equipped to take a lead in this important endeavor.